On the microstructure, hardness and wear behavior of Al-Fe-Cr quasicrystal reinforced Al matrix composite prepared by selective laser melting. (15th October 2017) - Kang, Nan; Fu, Yingqing; Coddet, Pierre; Guelorget, Bruno; Liao, Hanlin; Coddet, Christian
Abstract: Al91Fe4Cr5 quasicrystal (QC) reinforced α-Al matrix composite materials from the mixture of pure aluminum and Al65Cu20Fe10Cr5 QC powders were prepared by Selective Laser Melting (SLM) which can produce parts with sophisticated form and fine microstructure with near-zero material waste. The effects of process parameters (such as laser power and scanning speed) on the microstructure, hardness and wear behavior of SLMed composites were investigated with a special focus on the size and morphology of Al91 Fe4 Cr5 QC reinforcement. After laser melting process, an Al-rich QC phase (Al91 Fe4 Cr5 ) is formed. The grain size increases and its morphology changes from spherical to irregular with increment of laser power. Additionally, the sample obtained at relatively low laser power presents a mixed microstructure (partially melted QC, micro-QC and nano-QC) and high wear resistance. The instrumented indentation tests indicate that the partially melted QC particle present higher hardness than that of the other structure in the composite. Moreover, the wear mechanism changes from oxidation to delamination as the laser power increases. Graphical abstract: Highlights: Dense Al-Fe-Cr quasicrystal/α-Al composite was in-situ prepared by selective laser melting. Microcracks and fracture appear near oxygen-rich regions in the SLMed sample. Both the size and inner structure of the quasicrystal phase were affected by energy density. Sample with mixed quasicrystalline microstructure presents high wear resistance.